Genetic resources for enhancing drought tolerance from National Genebank collection of linseed (Linum usitatissimum L.) in India - Vikender Kaur; Devendra K. Payasi; Rakesh Choudhary; Vishnu Kumar; Shashank K. Yadav; Devender Singh; Vinay Kumar; Balram Jat; Deepa Garg; Vishal Kumar Gupta; Sudhir Kumar; Viswanathan Chinnusamy; et al. (Plant and Soil, 2025)

Anti-inflammatory Effects of Siponimod in a Mouse Model of Excitotoxicity-Induced Retinal Injury - Devaraj Basavarajappa; Vivek Gupta; Nitin Chitranshi; Deepa Viswanathan; Veer Gupta; Roshana Vander Wall; Viswanthram Palanivel; Mehdi Mirzaei; Yuyi You; Alexander Klistorner; Stuart L. Graham (Molecular Neurobiology, 2023)
Glaucoma is a leading cause of permanent blindness worldwide and is characterized by neurodegeneration linked to progressive retinal ganglion cell (RGC) death, axonal damage, and neuroinflammation. Glutamate excitotoxicity mediated through N-methyl-D-aspartate (NMDA) receptors plays a crucial role in glaucomatous RGC loss. Sphingosine 1-phosphate receptors (S1PRs) are important mediators of neurodegeneration and neuroinflammation in the brain and the retina. Siponimod is an immunomodulatory drug for multiple sclerosis and is a selective modulator of S1PR subtypes 1 and 5 and has been shown to have beneficial effects on the central nervous system (CNS) in degenerative conditions. Our previous study showed that mice administered orally with siponimod protected inner retinal structure and function against acute NMDA excitotoxicity. To elucidate the molecular mechanisms behind these protective effects, we investigated the inflammatory pathways affected by siponimod treatment in NMDA excitotoxicity model. NMDA excitotoxicity resulted in the activation of glial cells coupled with upregulation of the inflammatory NF-kB pathway and increased expression of TNFα, IL1-β, and IL-6. Siponimod treatment significantly reduced glial activation and suppressed the pro-inflammatory pathways. Furthermore, NMDA-induced activation of NLRP3 inflammasome and upregulation of neurotoxic inducible nitric oxide synthase (iNOS) were significantly diminished with siponimod treatment. Our data demonstrated that siponimod induces anti-inflammatory effects via suppression of glial activation and inflammatory singling pathways that could protect the retina against acute excitotoxicity conditions. These findings provide insights into the anti-inflammatory effects of siponimod in the CNS and suggest a potential therapeutic strategy for neuroinflammatory conditions.

A novel association of a polymorphism in the first intron of adiponectin gene with type 2 diabetes, obesity and hypoadiponectinemia in Asian Indians - Karani S. Vimaleswaran; Venkatesan Radha; Kandaswamy Ramya; Hunsur Narayan Sathish Babu; Nageshappa Savitha; Venkataramaiah Roopa; Dhar Monalisa; Raj Deepa; Saurabh Ghosh; Partha P. Majumder; M. R. Sathyanarayana Rao; Viswanathan Mohan (Human Genetics, 2008)